A comparison of low dose tiletamine‐zolazepam or acepromazine combined with methadone for pre‐anaesthetic medication in cats. (2nd July 2014) - Mair, Alastair; Kloeppel, Heide; Ticehurst, Kim
Abstract Objective To compare the level of sedation, cardiorespiratory changes, and quality of recovery in cats receiving methadone plus either low dose tiletamine‐zolazepam or acepromazine for premedication prior to general anaesthesia for neutering. Study design Prospective, randomized, blinded clinical study. Animals Twenty cats 0.54 ± 0.12 years‐old (mean ± SD), weighing 3.17 ± 0.65 kg (10 male and 10 female). Methods Cats were allocated randomly to receive intramuscularly either 0.03 mg kg−1 acepromazine (ACE) or 3 mg kg−1 tiletamine‐zolazepam (TZ), both regimens combined with 0.2 mg kg−1 methadone for premedication. Sedation was assessed 25 minutes after premedication using a visual analogue scale (VAS) and a simple descriptive scale (SDS). Anaesthesia was induced with alfaxalone and maintained with isoflurane. Physiological parameters were recorded at 1, 3 and 5 minutes post‐endotracheal intubation. Recovery from cessation of isoflurane was timed and quality assessed using a SDS and a VAS. Data was analysed with Mann–Whitney U‐test, students t‐test, anova or ordinal logistic regression as relevant. Significance was taken as p < 0.05. Results Sedation was more pronounced in TZ than ACE as indicated by higher VAS (67 ± 21 versus 13 ± 5) and SDS scores [4 (1–4) versus 1 (0–1)]. Following sedation, Heart (HR) and respiratory (fR) rates did not differ between groups. After anaesthetic induction, at times 1, 3 and 5 HR, systolic arterial pressure and end tidal carbon dioxide were significantly higher and fR was significantly lower in TZ than ACE. Recovery quality was similar between groups. In both groups, times to extubation, head lift and sternal recumbency were similar, but time (minutes) until standing was significantly longer in TZ (31 ± 16) than ACE (18 ± 11). Conclusion and clinical relevance Low dose tiletamine‐zolazepam combined with methadone provided superior sedation to ACE. Recovery quality was similar, although time to standing was longer.